Semester Credit System Program Evaluation at MTsN 2, Kediri City - Muhammad Syahrul Munir; Muhammad Akhsanul Muhtadin; Moch. Agung Lukman Septiansyah (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2022)
Education is needed by every student, so education must be in accordance with the needs needed by students. As is currently developing, namely education with a semester credit system (SKS). We often hear SKS in tertiary institutions as a unit of measurement for learning load. However, now SKS has begun to be implemented in junior high and high school. This study aims to find out how to evaluate the context of SKS program at MTsN 2 Kota Kediri, how to evaluate the input of SKS program at MTsN 2 Kota Kediri, how to evaluate the process of implementing SKS program at MTsN 2 Kota Kediri, how to evaluate the product of SKS program at MTsN 2 Kota Kediri. In this study a qualitative approach was used and the type of evaluation research was the CIPP model (Context, Input, Process, Product). Collecting data in this study using observation, documentation and in-depth interviews. The results of this study indicate that schools organize SKS to provide services to students according to their talents, interests and abilities, but there are problems in context evaluation, namely the understanding of participants and students' parents of SKS program is still lacking, in terms of assessing human resource input it still needs to be improved , in terms of process evaluation there were still difficulties in preparing and distributing Independent Learning Activity Unit books, and in terms of product evaluation it was considered good because there were students who won and could study in 2 years.